ANALISIS PERANAN SUBSEKTOR PERIKANAN TERHADAP PENINGKATAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN BERAU - Tustam (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
The purpose of the research was to find out and analyze the Analysis of the Role of the Fisheries Subsector on the Increase in Gross Regional Domestic Product (GDP) in Berau Regency. The research was conducted to the Fisheries Service and the Central Statistics Agency of Bearu Regency. Based on the results of the study, it can be seen that the contribution of the fisheries sub-sector to GDP between 2017-2021 was 0.04%, and in 2020 there was a slight decrease due to the occurrence of covid 19 but the decline has increased again, the fisheries sector every year has experienced a fairly good increase in fisheries in Berau Regency. From 2017 - 2021 GDP growth in Berau Regency of 0.5% - 5.3% can be seen that the growth of Gross Regional Domestic Product fluctuates and increases every year. This means that the role of the fisheries subsector has a positive effect on GDP.